The Secret Race : Inside the Hidden World of the Tour de France : Doping, Cover-Ups, and Winning at All Costs - Hamilton, Tyler; Coyle, Daniel (London Bantam Press, 2012)
Inside the Hidden World of the Tour de France : Doping, Cover-Ups, and Winning at All Costs.
Include Further Reading.
English Biography.
Keywords: Tour de France (Bicycle race) -- Hamilton, Tyler, 1971- -- Armstrong, Lance